Peculiarities of Psychological Readiness Structure of Mobilized Persons with Different Military Service Experience - Nikitenko, Hanna (Psychological Prospects Journal, 2018)
The article represents the research results of the differences in manifestation of internal and external factors of the psychological readiness structure of mobilized persons with different military service experience (persons, who do not have any military service experience, have only compulsory military service experience (from 9 months to 1 year) and have contract service experience (from 2 years)). The external factor of psychological readiness combines socio psychological, problem orientational and socially active components. And the internal factor consists of emotionally volitional, motivational, personality, behavioral, cognitive prognostic and cognitive reflexive components. With the help of Student’s t-test for independent (unpaired) samples has been determined that mobilized persons without military experience have lower level by the general indicators of the internal factor components formation of the structure of psychological readiness to the military service, than mobilized persons with experience of compulsory and contract military service, lower level of such internal components formation as emotionally volitional, behavioral and cognitive reflexive. Mobilized persons with contract service experience have higher level of formation of personality (internal), socially active (external) components and general parameter of the external factor components formation of the structure of psychological readiness, than mobilized persons with compulsory military service experience and without military service experience. The motivational component of the internal factor of the structure of psychological readiness is more formed in persons with contract military service experience than in persons without it. It has been also determined that the bigger is the military service experience of mobilized persons, the higher is the level of formation of the whole structure of psychological readiness to the military service.